2019
DOI: 10.1111/jam.14165
|View full text |Cite
|
Sign up to set email alerts
|

The potential of cadmium ion-immobilized Rhizobium pusense KG2 to prevent soybean root from absorbing cadmium in cadmium-contaminated soil

Abstract: Aims Because the effect of Cd2+‐immobilized microbe on Cd uptake of plants in Cd‐contaminated soil remains underexplored, this study focuses on the effect of Cd2+‐immobilized rhizobia on Cd uptake of soybean. Methods and Results Strain KG2 from soybean nodule was identified as Rhizobium pusense KG2 by phylogenetic analysis. Rhizobium pusense KG2 showed the 120 mg l−1 of minimal lethal concentration for Cd2+. In 50 and 100 mg l−1 of Cd2+ liquid, approximately 2 × 1010 cells removed 56·71 and 22·11% of Cd2+, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In agreement, the phylum Proteobacteria has previously been reported to be associated with Cd. A large number of isolated and identified strains that resisted Cd or absorbed Cd belong to Proteobacteria and include Burkholderia (Wang et al, 2020), Sphingomonas (Cheng et al, 2021), Pseudomona (Chellaiah, 2018), and Rhizobium (Li et al, 2019). Also many Gram-negative bacteria belonging to Proteobacteria such as Acinetobacter, Ralstonia (also named Cupriavidus) and Comamonas exclusively exist in a Cd-cultivation library of mine tailing (Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, the phylum Proteobacteria has previously been reported to be associated with Cd. A large number of isolated and identified strains that resisted Cd or absorbed Cd belong to Proteobacteria and include Burkholderia (Wang et al, 2020), Sphingomonas (Cheng et al, 2021), Pseudomona (Chellaiah, 2018), and Rhizobium (Li et al, 2019). Also many Gram-negative bacteria belonging to Proteobacteria such as Acinetobacter, Ralstonia (also named Cupriavidus) and Comamonas exclusively exist in a Cd-cultivation library of mine tailing (Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of antioxidant enzyme system under heavy metal stress can help plants to reduce ROS accumulation (Li et al 2019…”
Section: Resultsmentioning
confidence: 99%
“…Some microorganisms also can immobilize heavy metal ions. Li et al 37 reported that the Rhizobium pusense KG 2 can immobilize Cd 2+ from soil. Yang et al 17 studied that hybrid bio-nanocomposites of fungal hyphae and nano-hydroxyapatites immobilize Cd and Pb in contaminated soils suggested it can be recognized as a promising soil amendment candidate.…”
Section: Resultsmentioning
confidence: 99%